THE EFFECT OF IVABRADINE AND OMEGA-3 POLYUNSATURATED FATTY ACIDS FOR QUALITY OF LIFE OF PATIENTS WITH HEART FAILURE - Федоров, С. В.; Глушко, Л. В.; Медвідь, А. Б. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Pulse, 2019)
The effects of ivabradine and omega-3 polyunsaturated fatty acids (ω-3 PUFA) for quality of life (QoL) of patients with heart failure (HF) were studied. 357 patients with ischemic HF and sinus rhythm were randomized into four groups (due management). QoL was evaluated by MHFLQ and EuroQol-5D questionnaires. Established, that all medication’s schemes caused to improving of QoL of observed patients with HF, but not had influence for psychological status. More strong dynamics of QoL increase was observed in group with additional usage of Ivabradine and ω-3 PUFA. Additional prescription of Ivabradine was more effective for pain/fatigue reduction (OR=2,53; 95% СІ 1,14-5,34; р=0,03).